2021
DOI: 10.22491/2357-9730.108236
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence algorithm for the histopathological diagnosis of skin cancer

Abstract: Introduction: Cutaneous neoplasms are the most common cancers in the world, and have high morbidity rates. A definitive diagnosis can only be obtained after histopathological evaluation of the lesions. To develop an artificial intelligence program to establish the histopathological diagnosis of cutaneous lesions.Methods: A deep learning program was built using three neural network architectures: MobileNet, Inception and convolutional networks. A database was constructed using 2732 images of melanomas, basal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…Most deep-learning diagnostic applications for histological images are for the differentiation between melanoma and nevi [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. However, multiple studies show applications in the differentiation between melanoma, nevi, and normal skin [ 34 , 35 ]; and differentiation between melanoma and nonmelanoma skin cancers [ 36 , 37 , 38 ]. Several studies showed deep-learning applications for the segmentation of whole tumor regions [ 39 , 40 , 41 , 42 ] or individual diagnostic markers such as mitotic cells [ 43 , 44 ], melanocytes [ 45 , 46 ], and melanocytic nests [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most deep-learning diagnostic applications for histological images are for the differentiation between melanoma and nevi [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. However, multiple studies show applications in the differentiation between melanoma, nevi, and normal skin [ 34 , 35 ]; and differentiation between melanoma and nonmelanoma skin cancers [ 36 , 37 , 38 ]. Several studies showed deep-learning applications for the segmentation of whole tumor regions [ 39 , 40 , 41 , 42 ] or individual diagnostic markers such as mitotic cells [ 43 , 44 ], melanocytes [ 45 , 46 ], and melanocytic nests [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pelo contrário, parafraseando a citação, essa individuação 'aumenta desmensuradamente' a potência do coletivo, as histórias aumentam 'desmensuradamente' a potência da História. Aliás, não há História, não há o que possamos qualificar de histórico sem que pulsem aí as histórias de si (Kuiava;Wiacek, 2009, p. 171).…”
Section: Curadoria E Procedimentos De Pesquisa Entre O Cinema E a Edu...unclassified
“…On the contrary, to paraphrase the quote, this individuation 'increases immeasurably' the power of the collective, stories increase 'immeasurably' the power of History. In fact, there is no History, there is nothing that we can describe as historical without the stories of the self-pulsating there (Kuiava;Sierra;Wiacek, 2009, p. 171).…”
Section: Curation and Research Procedures Between Cinema And Educationmentioning
confidence: 99%